An assessment of written leaflets for enhancing patient education and counselling on asthma and chronic obstructive pulmonary disease in the implementation of a New Medicine Service in Poland - Weronika Guzenda; Magdalena Jasińska-Stroschein; Aleksandra Wawrowska; Olga Sierpniowska; Artur Jędra; Piotr Przymuszała; Piotr Dąbrowiecki; Patrycja Wiśniewska; Magdalena Waszyk-Nowaczyk (Scientific Reports)
Abstract In recent years, an increasing number of people have been struggling with chronic respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD). Experienced pharmacists may play a crucial role in spreading knowledge by explaining what these diseases are and why it is important to take medications correctly. They could provide education in pharmaceutical care and professional counselling, e.g., leaflets that help people better absorb and remember the information. The aim of the study was to assess patients’ knowledge before and after they read the prepared educational materials on asthma and COPD as part of the New Medicine Service (NMS) and to gather their opinions on them. This study was carried out via proprietary questionnaires from March 2023 to January 2024 in Poznan and Lodz. A knowledge test, which was completed by patients before and after they read the brochure on asthma and COPD, was used, as was a satisfaction questionnaire that subjectively evaluated the proposed educational material. The study was conducted in various settings - community pharmacies and general practitioners’ clinics. A total of 690 respondents participated in the study and completed the surveys (350 and 340 regarding asthma and COPD, respectively). In a pre-post analysis, the respondents obtained statistically higher scores on knowledge tests for both asthma (p < 0.001) and COPD (p < 0.001) after reading the brochure than before, confirming an increase in their knowledge of the subject matter. The respondents also significantly higher rated their self-assessed knowledge of these diseases after reading the leaflets than before. The materials provided for asthma and COPD patients were also highly assessed by the respondents in terms of their interest in them and their aesthetics, clarity, usefulness, and comprehensibility. The described materials on asthma and COPD, which are used as part of the NMS, can be useful in enhancing patients’ knowledge of both conditions. They can complement the service by providing additional information, supporting the treatment process, and helping patients better understand asthma and COPD.